Detuning dependent Rabi oscillations of a single molecule. (26th April 2019) - Rezai, Mohammad; Wrachtrup, Jörg; Gerhardt, Ilja
Abstract: A single organic dye molecule at cryogenic conditions is resonantly excited in a confocal microscope. Under strong laser illumination it undergoes Rabi oscillations. Mathematically, this was well described and had been experimentally implemented. These oscillations can be measured as side-bands on their resonance fluorescence, e.g. in the Mollow-Triplet. An alternative method is to research this effect by an analysis of the single molecule anti-bunched photon statistics. This has been performed in this work. Here we research on the detuning dependence of this signal—it is experimentally demanding since the utilized laser might drift or single emitters are not necessarily spectrally stable enough, such that the spectrum can be measured indefinitely. We therefore apply a measurement technique in which the photon correlation signal is acquired in detuning dependent steps. This is performed by continuous laser sweeps over the single molecule excitation spectrum. A single recording of the anti-bunched photons takes 20–50 ms. After approx. 1 h of repetitive laser detunings a full anti-bunching curve is reconstructed for each spectral position. An alternative technique with 100 ns laser pulses allows us to acquire a set of comparable data. Our study is derived from a single dibenzanthanthrene molecule with a natural linewidth of 2 π ×16 MHz. It emits under resonant excitation more than 380.000 photons per second. Under spectral detuning, Rabi-oscillations are observed up to Ω Rabi  = 2 π ×160 MHz.